2015
DOI: 10.1002/rcm.7249
|View full text |Cite
|
Sign up to set email alerts
|

Diet-to-female and female-to-pup isotopic discrimination in South American sea lions

Abstract: Only the stable isotope ratios in pup blood are good proxies of the individual lactating females. Thus, we suggest that blood components are more appropriate to quantify the feeding habits of wild individuals of this species. Furthermore, because female-to-pup discrimination factors for blood components did not differ between captive and wild individuals, we suggest that results for captive experiments can be extrapolated to wild South American sea lion populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…For all tissue types, the Δ 13 C values calculated from lipid-corrected prey were within the range of calculated Δ 13 C values from studies where the prey had been lipid-extracted, including the captive sea otter study [39] . The one exception was that our estimates of the diet-to-RBC Δ 13 C values (+1.4 to +1.9‰) were considerably greater than the value of +0.2‰ reported by Drago et al [18] for South American sea lions ( Otaria flavescens ). The similarities among ours and previous studies for estimates of Δ 13 C values calculated using lipid-corrected prey suggest that differences among studies in prey lipid content may partially explain why we observed higher Δ 13 C values from bulk prey than found in previous studies.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…For all tissue types, the Δ 13 C values calculated from lipid-corrected prey were within the range of calculated Δ 13 C values from studies where the prey had been lipid-extracted, including the captive sea otter study [39] . The one exception was that our estimates of the diet-to-RBC Δ 13 C values (+1.4 to +1.9‰) were considerably greater than the value of +0.2‰ reported by Drago et al [18] for South American sea lions ( Otaria flavescens ). The similarities among ours and previous studies for estimates of Δ 13 C values calculated using lipid-corrected prey suggest that differences among studies in prey lipid content may partially explain why we observed higher Δ 13 C values from bulk prey than found in previous studies.…”
Section: Discussioncontrasting
confidence: 98%
“…We used whole prey instead of only fish muscle for the prey isotopic composition, whereas several of these previous studies used only fish muscle [6,15,18] . Fish muscle typically has higher δ 15 N values than whole fish [31] , which results in lower TDF values than those calculated using isotope ratios from whole fish [31] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stable isotope values of the white muscle of the herring ( δ 13 C = −18.6‰ ± 0.3‰; δ 15 N = 12.6‰ ± 0.5‰) and capelin ( δ 13 C = −20.6‰ ± 0.3‰; δ 15 N = 11.7‰ ± 0.5‰) used to feed the captive sea lions had been previously reported by Drago et al . (). Vibrissae were collected during one of the health checks conducted by the veterinary staff of L'Oceanogràfic on 22 February 2012.…”
Section: Methodsmentioning
confidence: 97%